National Neonatology Forum Clinical Decision-making for Infants Born at the Margin of Viability: A Modified Delphi Consensus Statement - Rhishikesh Thakre; Srinivas Murki; Lalan Kumar Bharti; Thangaraj Abiramalatha; Suman Rao P. N.; Reeta Bora; Shiv Sajan Saini; Giridhar Sethuraman; Anitha Haribalakrishna; Shalini Tripathi; Suksham Jain; Supreet Khurana; et al. (Journal of Neonatology, 2026)
Infants born at the margins of viability represent a gestational-age window characterized by uncertain survival and a high risk of mortality and long-term neurodevelopmental impairment. Evidence to guide management in low- and middle-income countries remains limited, and in India, decision-making is further influenced by heterogeneity in neonatal intensive care infrastructure, availability of trained personnel, access to perinatal services, and socio-economic and cultural disparities. Recognizing these challenges, an expert panel convened under the aegis of the National Neonatology Forum developed consensus-based guidance for clinical decision-making in periviable infants. A structured modified Delphi process was employed to achieve agreement across key domains. The panel reached consensus on 41 statements addressing 11 prioritized clinical questions relevant to periviable care in the Indian context. These recommendations provide an evidence-informed and ethically grounded framework to support clinicians and families in complex decision-making at the limits of viability. The consensus reflects current expert agreement and may evolve with emerging evidence and future research.